Pemberdayaan Masyarakat Melalui Edukasi“Gizi Seimbang” Sebagai Upaya Pencegahan Stunting Pada Balita di Wilayah Kerja Puskesmas Hutabalang Tahun 2023 - Ramlan Nasution; Esrina Sinaga; Herawati Harahap (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2023)
Community service for the D-III Nursing Study Program in Central Tapanuli, Medan Ministry of Health Polytechnic, is carried out in the form of education about community empowerment through balanced nutrition education as an effort to prevent stunting. The target of service activities is 40 pregnant women and mothers with early childhood children who are in the working area of the Hutabalang Community Health Center. The aim of this Community Service is to realize community service as one of the Tri Darma activities of higher education, increase the knowledge of pregnant women and mothers with early childhood regarding stunting and balanced nutrition and provide training on how to make naget as an effort to minimize the occurrence of stunting in the work area. Hutabalang Health Center, Lack of Knowledge about Stunting is caused by multi-dimensional factors and is not only caused by poor nutrition experienced by pregnant women and toddlers. Several factors that influence the incidence of stunting include maternal factors, home environmental factors, low food quality, inadequate feeding, food and drink safety, breastfeeding (breastfeeding phase), infection, political economy, health and health services, education, social and culture, agricultural and food systems, water, sanitation and the environment. Community service activities carried out in the working area of the Hutabalang Health Center, Badiri District, Central Tapanuli Regency by providing education to participants by means of lectures and question and answer/discussion, succeeded in increasing the knowledge of pregnant women and mothers with early childhood. Before the education was carried out, the level of knowledge in the good category was 40% and after the education was carried out it increased to 85%.